2016
DOI: 10.1002/admi.201600320
|View full text |Cite
|
Sign up to set email alerts
|

Interface Effect on Efficiency Loss in Organic Light Emitting Diodes with Solution Processed Emitting Layers

Abstract: easily achieved with sequential deposition, the redissolution of the preceding layer by solvents used in the subsequent layers is a challenge for solution processed OLEDs during the multilayer fabrication process. [ 4 ] To get around this problem, cross-linkable hole transporting layers (HTLs) are typically used such that subsequent deposition of the emitting layer (EML) would not damage the underlying HTL during processing. [5][6][7][8][9][10][11] To fi nish the device fabrication, evaporated electron transpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 35 publications
2
14
0
Order By: Relevance
“…Intersystem crossing (ISC) from singlet to triplet spin‐pair states, including polaron pairs (PP 1 and PP 3 ) and charge‐transfer states (CT 1 and CT 3 ), and their reverse ISC (RISC) in exciplex‐based organic light‐emitting diodes (EB‐OLEDs) can efficiently tune the singlet/triplet ratio and thus are important spin‐mixing processes for attaining high‐efficiency device performance. [ 1,2 ] However, few tool can directly probe these ISC and RISC processes previously. This is because the optoelectronic properties of OLEDs are usually affected by various physical microscopic processes of spin‐pair states in the device, such as ISC, RISC, singlet fission (S 1 + S 0 → T 1 + T 1 ), triplet fusion (T 1 + T 1 → S 1 + S 0 ), and triplet‐charge annihilation (TQA) processes.…”
Section: Introductionmentioning
confidence: 99%
“…Intersystem crossing (ISC) from singlet to triplet spin‐pair states, including polaron pairs (PP 1 and PP 3 ) and charge‐transfer states (CT 1 and CT 3 ), and their reverse ISC (RISC) in exciplex‐based organic light‐emitting diodes (EB‐OLEDs) can efficiently tune the singlet/triplet ratio and thus are important spin‐mixing processes for attaining high‐efficiency device performance. [ 1,2 ] However, few tool can directly probe these ISC and RISC processes previously. This is because the optoelectronic properties of OLEDs are usually affected by various physical microscopic processes of spin‐pair states in the device, such as ISC, RISC, singlet fission (S 1 + S 0 → T 1 + T 1 ), triplet fusion (T 1 + T 1 → S 1 + S 0 ), and triplet‐charge annihilation (TQA) processes.…”
Section: Introductionmentioning
confidence: 99%
“…As it can be seen in Figure D, we observe a noticeably smaller efficiency roll‐off at higher luminance levels for Device B, implying a better charge balance resulting from a more effective hole blocking under higher biases . We have previously shown that a deeper HOMO for an effective hole‐blocking ETL is required for solution processed EMLs due to a wider band‐broadening and the energetic disorder at the EML/ETL interface . As we have shown in Figure D, the EQE of Device A reduces to 5% at a high luminance of 2000 cd m −2 from a maximum EQE value of 12%, showing a large efficiency roll‐off of 58%.…”
Section: Resultsmentioning
confidence: 99%
“…However, some challenges related to the IJP OLED technology have to be overcome. For example, intermixing of successive solution processed layers resulting in the damage of previously deposited layers was shown to happen and to be hard to prevent . Such undefined interfaces are critical for OLED performance .…”
Section: Ijp Solvents Used To Process Polymer X‐pomentioning
confidence: 99%